Stargate. The ark of truth - Lenic, John G.; Cooper, Robert C., 1969 or 70-; Browder, Ben, 1962-; Shanks, Michael, 1970-; Tapping, Amanda, 1965-; Black, Claudia, 1972-; Bridges, Beau.; Maybee, Spencer; Christopher, Martin; Wright, Brad.; Glassner, Jonathan; Kawoosh! Productions VII (Firm); et al. (Beverly Hills, Calif. : 20th Century Fox Home Entertainment [distributor], 2008)
SG-1 searches for an ancient weapon which could help them defeat the Ori, and discover it may be in the Ori's own home galaxy. As the Ori prepare to send ships through to the Milky Way to attack Earth, on board the Odyssey, SG-1 travels to the Ori galaxy. The International Oversight Committee has their own plans and SG-1 finds themselves in a distant galaxy fighting two powerful enemies.
Characters developed by Brad Wright & Jonathan Glassner.
Special features: Commentary with writer, director and producer Robert C. Cooper, actor Christopher Judge and director of photography Peter Woeste; "Stargate SG-1: The road taken: prelude to Stargate: The ark of truth" featurette; "The ark of truth: Stargate at Comic-con" featurette; "Uncovering The ark of truth" featurette; theatrical trailers.
Director of photography, Peter F. Woeste ; music, Joel Goldsmith ; production designer, James Robbins.
Ben Browder, Michael Shanks, Amanda Tapping, Christopher Judge, Claudia Black, Beau Bridges, Spencer Maybee, Martin Christopher.
Not rated.
DVD, region 1, widescreen (1.78:1) presentation; Dolby Digital 5.1 surround, Dolby Digital surround; dual layer.
Keywords: Galaxies -- Drama; Weapons, Ancient -- Drama; Space flight -- Drama; Milky Way -- Drama; Science fiction films; Video recordings for the hearing impaired; Fantasy films; Adventure films; Feature films